2021
DOI: 10.1007/s10072-021-05366-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of self-descriptive apathy assessment in patients with neurological form of Wilson’s disease

Abstract: Background and aim Apathy is one of the neuropsychiatric symptoms of Wilson’s disease (WD) which typically affects the brain’s fronto-basal circuits. Lack of agreed diagnostic criteria and common use of self-description assessment tools lead to underestimation of this clinical phenomenon. The aim of this study was to investigate whether subjective and informant-based clinical features of apathy in patients with WD enable clinicians to make a valid diagnosis. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Previous studies indicated that cognitive and psychiatric problems in WD patients might result from the joint abnormal functions of ITG, MFG [40,41] . Also, we located that reduced FC in the FPN network used to be negatively correlated with the UWDRS-N. Studies focusing on neuropsychological impairments in WD have demonstrate that patients with WD showing neurological signs present signi cant de cits in a wide range of cognitive domains [42,43] , and sufferers recruited in this study showcase impairments in executive function. It suggested that disruption in DMN, DAN, FPN networks and integrative conversations between them, which involve the failure of higher-order cognitive processes, might provide a neurophysiological account of the maladaptive daily behaviors of WD patients.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies indicated that cognitive and psychiatric problems in WD patients might result from the joint abnormal functions of ITG, MFG [40,41] . Also, we located that reduced FC in the FPN network used to be negatively correlated with the UWDRS-N. Studies focusing on neuropsychological impairments in WD have demonstrate that patients with WD showing neurological signs present signi cant de cits in a wide range of cognitive domains [42,43] , and sufferers recruited in this study showcase impairments in executive function. It suggested that disruption in DMN, DAN, FPN networks and integrative conversations between them, which involve the failure of higher-order cognitive processes, might provide a neurophysiological account of the maladaptive daily behaviors of WD patients.…”
Section: Discussionsupporting
confidence: 52%
“…The patients with dystonia may had difficulty finishing the tasks because of their inflexible movements. The more important reason was that the impairments in the prefrontal cortex (Leśniak et al., 2022 ). Highly sensitive to the dopaminergic environment, the prefrontal cortex is also related to executive functions (Ott & Nieder, 2019 ; Uddin, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Disease features correlate with the organs or tissues affected, which are mainly the liver and brain leading to hepatic cirrhosis, dysarthria, and dysphagia (Dusek et al., 2019 ). In addition, WD patients suffer from anxiety, depression, or other neurological symptoms (Leśniak et al., 2022 ). The percentage of WD patients with dystonia has been reported to range from 11% to 65% (Członkowska et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%